Design, synthesis and evaluation of sulfonylurea-containing 4-phenoxyquinolines as highly selective c-Met kinase inhibitors. Issue 13 (1st July 2019) - Nan, Xiang; Jiang, Yi-Fan; Li, Hui-Jing; Wang, Jun-Hu; Wu, Yan-Chao
Graphical abstract: Highlights: Sulfonylurea-containing 4-phenoxyquinolines are found to be new c-Met inhibitors. Most of the target compounds possess satisfactory anticancer activities. Compound13x has higher anticancer activities against 3 cell lines than foretinib. Compound 13x selectively inhibit c-Met versus 10 other RTK-family proteins. Abstract: Deregulation of receptor tyrosine kinase c-Met has been reported in human cancers and is considered as an attractive target for small molecule drug discovery. In this study, a series of 4-phenoxyquinoline derivatives bearing sulfonylurea moiety were designed, synthesized and evaluated for their c-Met kinase inhibition and cytotoxicity against tested four cell lines in vitro. The pharmacological data indicated that most of the tested compounds showed moderate to significant potency as compared with foretinib, with the most promising compound13x (c-Met kinase IC50 = 1.98 nM) demonstrated relatively good selectivity versus 10 other tyrosine kinases and remarkable cytotoxicities against HT460, MKN-45, HT-29 and MDA-MB-231 with IC50 values of 0.055 µM, 0.064 µM, 0.16 µM and 0.49 µM, respectively. The preliminary structure activity relationships indicated that a sulfonylurea moiety as linker as well as mono-EGWs (such as R1 = 4-F) on the terminal phenyl rings contributed to the antitumor activity.